Guselkumab plus golimumab combination therapy versus guselkumab or golimumab monotherapy in patients with ulcerative colitis (VEGA): a randomised, double-blind, controlled, phase 2, proof-of-concept trial. (April 2023) - Feagan, Brian G; Sands, Bruce E; Sandborn, William J; Germinaro, Matthew; Vetter, Marion; Shao, Jie; Sheng, Shihong; Johanns, Jewel; Panés, Julián; ,; Tkachev, Alexander; Kalimullina, Dilara; et al.
Summary: Background: Despite the introduction of new monoclonal antibodies and oral therapies for the treatment of ulcerative colitis, clinical remission rates remain low, underscoring the need for innovative treatment approaches. We assessed whether guselkumab plus golimumab combination therapy was more effective for ulcerative colitis than either monotherapy. Methods: We did a randomised, double-blind, controlled, proof-of-concept trial at 54 hospitals, academic medical centres, or private practices in nine countries. Eligible adults (aged ≥18 to 65 years) had a confirmed diagnosis of ulcerative colitis at least 3 months before screening and moderately-to-severely active ulcerative colitis (Mayo score 6–12) with a centrally-read baseline endoscopy subscore of 2 or higher. Patients were randomly assigned (1:1:1) using a computer-generated randomisation schedule to combination therapy (subcutaneous golimumab 200 mg at week 0, subcutaneous golimumab 100 mg at weeks 2, 6, and 10, and intravenous guselkumab 200 mg at weeks 0, 4, and 8, followed by subcutaneous guselkumab monotherapy 100 mg every 8 weeks for 32 weeks), golimumab monotherapy (subcutaneous golimumab 200 mg at week 0 followed by subcutaneous golimumab 100 mg at week 2 and every 4 weeks thereafter for 34 weeks), or guselkumab monotherapy (intravenous guselkumab 200 mg at weeks 0, 4, and 8, followed by subcutaneous guselkumab 100 mg every 8 weeks thereafter for 32 weeks). The primary endpoint was clinical response at week 12 (defined as a ≥30% decrease from baseline in the full Mayo score and a ≥3 points absolute reduction with either a decrease in rectal bleeding score of ≥1 point or a rectal bleeding score of 0 or 1). Efficacy was analysed in the modified intention-to-treat population up to week 38, which included all randomly assigned patients who received at least one (partial or complete) study intervention dose. Safety was analysed up to week 50, according to study intervention received among all patients who received at least one (partial or complete) dose of study intervention. This trial is complete and is registered with ClinicalTrials.gov, NCT03662542 . Findings: Between Nov 20, 2018, and Nov 15, 2021, 358 patients were screened for eligibility, of whom 214 patients were randomly assigned to combination therapy (n=71), golimumab monotherapy (n=72), or guselkumab monotherapy (n=71). Of the 214 patients included, 98 (46%) were women and 116 (54%) were men and the mean age was 38·4 years (SD 12·0). At week 12, 59 (83%) of 71 patients in the combination therapy group had achieved clinical response compared with 44 (61%) of 72 patients in the golimumab monotherapy group (adjusted treatment difference 22·1% [80% CI 12·9 to 31·3]; nominal p=0·0032) and 53 (75%) of 71 patients in the guselkumab monotherapy group (adjusted treatment difference 8·5% [–0·2 to 17·1; nominal p=0·2155). At week 50, 45 (63%) of 71 patients in the combination therapy group, 55 (76%) of 72 patients in the golimumab monotherapy group, and 46 (65%) of 71 patients in the guselkumab monotherapy group had reported at least one adverse event. The most common adverse events were ulcerative colitis, upper respiratory tract infection, headache, anaemia, nasopharyngitis, neutropenia, and pyrexia. No deaths, malignancies, or cases of tuberculosis were reported during the combination induction period. One case of tuberculosis was reported in the combination therapy group and one case of colon adenocarcinoma was reported in the guselkumab monotherapy group; both occurred after week 12. Two deaths were reported after the final dose of study intervention (poisoning in the combination therapy group and COVID-19 in the guselkumab monotherapy group). Interpretation: Data from this proof-of-concept study suggest that combination therapy with guselkumab and golimumab might be more effective for ulcerative colitis than therapy with either drug alone. These findings require confirmation in larger trials. Funding: Janssen Research and Development.